Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

Tectonic modulation of caldera volcanism on the South Aegean Volcanic Arc - Abigail Metcalfe; Tim Druitt; Katharina Pank; Steffen Kutterolf; Jonas Preine; Sarah Beethe; Axel Schmitt; Christian Hübscher; Paraskevi Nomikou; Thomas A. Ronge; Carole Berthod; Hehe Chen; et al. (Earth and Planetary Science Letters, 2025)

Vaccination against Hendra virus of previously unvaccinated mares and their foals demonstrates the effectiveness of the current prime and boost vaccination schedule for foals - Kimberley J. Carey; Ina Smith; Carol A. Hartley; Kirsten E. Bailey; Kath McIntosh; Christopher C. Broder; James R. Gilkerson (Veterinary Microbiology, 2025)

Stacking and Intersecting Nitrogen 4Rs on Potato: Economic Analysis - Samuel H. Stapley; Christopher S. McIntosh; Matt A. Yost; Neil C. Hansen; Ryan C. Christensen; Bryan G. Hopkins (American Journal of Potato Research, 2025)
The 4Rs of nutrient management is an initiative to balance economics with sustainability. The objective was to evaluate individual and stacked 4R practices on potato ( Solanum tuberosum L.) profitability. Treatments included all combinations of two nitrogen (N) sources (urea or polymer coated urea [PCU]), two rates (82 or 100%), and/or two timing/placements (at emergence or split-applied). Gross income and net profit were determined using yields, market sale data, and costs. Total gross income was greatest for PCU split applied and PCU at emergence in 2020 and 2023, respectively. Gross income and net profit were higher for the full rate for PCU compared to urea. The detrimental effect of the reduced rate disappeared with PCU, but not urea. A reduced rate of PCU was similar to a full rate of split applied urea. These data suggest that PCU is a profitable N source for potato even at reduced rates.

Economic Impact of Globodera Pallida on the Idaho Economy - Samjhana Koirala; Philip Watson; Christopher S. McIntosh; Louise-Marie Dandurand (American Journal of Potato Research, 2020)

Manipulation of Physiological Seed Age of Russet Burbank and Ranger Russet Potatoes – Economic Evaluation - Sarad Nepal; Christopher S. McIntosh; Michael K. Thornton; Nora Olsen; Phil Nolte; Paul E. Patterson (American Journal of Potato Research, 2016)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Potato Seed Piece Size, Spacing, and Seeding Rate Effects on Yield, Quality and Economic Return - William H. Bohl; Jeffrey C. Stark; Christopher S. McIntosh (American Journal of Potato Research, 2011)

Identity Preservation Systems for Genetically Modified Potatoes - Elliot A. Toevs; Joseph F. Guenthner; Aaron J. Johnson; Christopher S. McIntosh; Michael K. Thornton (American Journal of Potato Research, 2011)

The Role of the Intestinal Lymphatics in the Absorption of Two Highly Lipophilic Cholesterol Ester Transfer Protein Inhibitors (CP524,515 and CP532,623) - Natalie L. Trevaskis; Claire L. McEvoy; Michelle P. McIntosh; Glenn A. Edwards; Ravi M. Shanker; William N. Charman; Christopher J. H. Porter (Pharmaceutical Research, 2010)

Statistical Analysis of the Laboratory Methods Used to Detect Potato Virus Y - Yuliya V. Bolotova; Alexander V. Karasev; Christopher S. McIntosh (American Journal of Potato Research, 2009)

Application of 16S rDNA-DGGE and Plate Culture to Characterization of Bacterial Communities Associated with the Sawfly, Acantholyda erythrocephala (Hymenoptera, Pamphiliidae) - Viviane Zahner; Christopher J. Lucarotti; Douglas McIntosh (Current Microbiology, 2008)

Price Volatility of Idaho Fresh Potatoes: 1987–2007 - Kalamani Muthusamy; Christopher S. McIntosh; Yuliya Bolotova; Paul E. Patterson (American Journal of Potato Research, 2008)

Optimal Crop Rotation of Idaho Potatoes - Penny Myers; Christopher S. McIntosh; Paul E. Patterson; R. Garth Taylor; Bryan G. Hopkins (American Journal of Potato Research, 2008)

40Ar/39Ar dating of the eruptive history of Mount Erebus, Antarctica: summit flows, tephra, and caldera collapse - Christopher J. Harpel; Philip R. Kyle; Richard P. Esser; William C. McIntosh; David A. Caldwell (Bulletin of Volcanology, 2004)

Swarming and mating behavior of a mayfly Baetis bicaudatus suggest stabilizing selection for male body size - Barbara L. Peckarsky; Angus R. McIntosh; Christopher C. Caudill; Jonas Dahl (Behavioral Ecology and Sociobiology, 2002)